Syntactic Phrases Analysis in Disney Wish Movie - Antonia, Desi Kumala Sari; Tuminah, Tuminah (Jurnal Simki Pedagogia, 2025)
This research analyzed syntactic phrases that are used in the dialogue of the Disney Wish movie. This research aims to find out the types of phrases and the most common phrases that are used by the main characters in the Disney Wish movie. The methodology used in this research is a qualitative method with a descriptive approach. In data collection, the researcher uses Simak Bebas Libat Cakap (SBLC) and the note-taking technique. The research data is the types of phrases and the most common phrases. The research sources is a movie accessed from Disney+ Hotstar platform and a movie transcription. The researcher employs three steps in data analysis: data reduction, data display, and drawing conclusions. The research results showed that from 145 total of phrases, the researcher found four types of phrases, namely Noun Phrase (NP) which 87 occurrences or 60,00%, Verb Phrase (VP) which 36 occurrences or 24,83%, Adjective Phrase (AdjP) which 3 occurrences or 2,07%, and Preposition Phrase (PP) which 19 occurrences or 13,10%. The most common phrases that are used by the main characters in the Disney Wish movie is noun phrase. In English education, especially for teachers who teach English, this research can contribute as a teaching tool to teach about phrases.